Myanmar under reform: Emerging pressures on water, energy and food security. (17th December 2013) - Kattelus, Mirja; Rahaman, Muhammad Mizanur; Varis, Olli
Abstract Myanmar's water‐related sectors are subject to intensive changes, as the country's abundant land and water resources provide substantial scope for development. Recent steps towards economic reform in Myanmar have led to a surge of foreign investment directed towards intensified natural resource extraction. Both the agricultural and the energy sector are increasingly affected by foreign investments that will impact the status of water, energy and food security in the country. With these on‐going developments, Myanmar's future is largely dependent on how its natural resources are managed and how the benefits from the resource extraction are shared. With various institutional changes and new actors welcomed to the sectors, existing livelihoods and ecosystems dependent on the land and water resources are to face increasing competition for the shared resources, while lacking secured access to them. There are increasing concerns that this sectoral development is occurring at the expense of environmental and social sustainability. As one way to tackle these challenges, the water‐energy‐food nexus approach could help in finding synergies and co‐benefits across sectors by addressing the imbalances along the nexus and externalities derived from the on‐going intensification.